Site Survey - Singh, Sagar (Indian Forester, 1967)
This paper deals with the standards and procedure adopted in the field survey undertaken by the author in J.K. Paper Mill. (Orissa State) for systematic planning of large scale plantation programme mainly of fast growing pulpable hardwoods like Eucalyptus, Ailanthus, Cassia siamia Erythrina, Gliricidia maculala, etc. In the absence of any standard practice on the subject, it may prove of some use to othero for similar purpose.